The Value of Settlement Local Wisdom in Nagari Pariangan, West Sumatra Province - Harne Julianti Tou; Melinda Noer; Helmi Helmi; Sari Lenggogeni (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
This research examines the concept and empirical basis of settlement and local wisdom. Settlements contain residential environments along with facilities and infrastructures to support functions. Local wisdom is local ideas that have good values or norms practiced and believed to be referenced in everyday life. This study observes the implementation of local wisdom in settlement management, which aims to assess the local wisdom contained in settlements Nagari Pariangan, Tanah Datar Regency, West Sumatra Province using a qualitative descriptive method. The novelty of this research reveals contextually the local wisdom of settlements in Nagari Pariangan, which has its characteristics, including Rumah Gadang and surau (prayer houses) owned by each suku (ethnic group), as well as tapian (banks) used for common purposes. Results of this study show that the values of local wisdom in settlements in Nagari Pariangan are manifested in the value of environmental conservation and social values, where these values are not fully maintained, and some have not been continued or implemented until now. To maintain the values of local wisdom can be continued it is necessary to provide learning to the younger generation and to activate the surau as a mean of learning and education.